Industrial noise and tooth wear – Experimental study - Cavacas, M. A. (2015)
"Tooth wear is a complex multifactorial process that involves the loss of hard dental tissue. Parafunctional habits have been mentioned as a self-destructive process caused by stress, which results in hyperactivity of masticatory muscles. Stress manifests itself through teeth grinding, leading to progressive teeth wear. The effects of continuous exposure to industrial noise, a “stressor” agent, cannot be ignored and its effects on the teeth must be evaluated. Aims: The aim of this study was to ascertain the effects of industrial noise on dental wear over time, by identifying and quantifying crown area loss. Material and Methods: 39 Wistar rats were used. Thirty rats were divided in 3 experimental groups of 10 animals each. Animals were exposed to industrial noise, rich in LFN components, for 1, 4 and 7 months, with an average weekly exposure of 40 hours (8h/day, 5 days/week with the weekends in silence). The remaining 9 animals were kept in silence. The areas of the three main cusps of the molars were measured under light microscopy. Statistical analysis used: A two-way ANOVA model was applied at significance level of 5%. Results: The average area of the molar cusps was significantly different between exposed and non-exposed animals. The most remarkable differences occurred between month 1 and 4. The total crown loss from month 1 to month 7 was 17.3% in the control group, and 46.5% in the exposed group, and the differences between these variations were significant (p<0.001). Conclusions: Our data suggest that industrial noise is an important factor in the pathogenesis of tooth wear."